Counter-terrorism measures & human right violations an international legal perspective - Rastegari, Behnam; Rohaida Nordin (Penerbit Universiti Kebangsaan Malaysia, 2020)
Counter-terrorism a series of offensive action to eliminate terrorist activities are different from anti-terrorism actions. Counter-terrorism measures are usually implemented following terrorist activities to cripple the ability of the terrorist, while anti-terrorism measures aim to identify the causes and roots of terrorism in order to prevent the possibility of terrorist attacks.